(untitled) - Stanley, William D. (Australia, 2006)
This book develops a solid understanding of the general principles that govern all communications systems. Topics include traditional analog communication techniques such as AM and FM, modern digital systems, radar, wireless, networking, consumer communications systems, and many other areas. Practical applications are stressed with an emphasis on signal processing at a systems level, in order to provide a better background for readers as technology advances and new integrated circuits become available
Keywords: Telecommunication,Data transmission systems,Computer networks,Điện tử viễn thông